Pengaruh Brand Association terhadap Keputusan Pembelian Air Mineral Merek Aqua - Fernante Muhibi; Syaifuddin Fahmi (STIE Kertanegara Malang, 2019)
This study aims to describe whether brand association influences the purchasing decision of Aqua brand mineral water customers (PT Livia Mandiri Sejati Kota Pasuruan). The method used in this research is descriptive method with quantitative approach. Where the brand association factor consists of, price, product quality, brand, and promotion. Of all the factors whether it influences the decision to purchase Aqua brand mineral water in Pasuruan City. This research was conducted using a case study method where data were obtained through questionnaires to 135 respondents. The population in this study are consumers in the Pasuruan city area who have ever bought or consumed Aqua. The technique in sampling is non probability sampling with convenience sampling type. The data collection method used in this study was a questionnaire. Furthermore, from the data obtained normality test, multicollinearity test, heteroscedacity test, multiple linear regression test, F test, t test and coefficient of determination test. From the results of data analysis, brand association factors simultaneously influence the decision to purchase Aqua brand mineral water in the Pasuruan City area.